Outlaw - West, Charles (Berkley, 2022)
"When war came to the Shenandoah Valley, Matt Slaughter and his older brother, Owen, joined the Confederate army. But three years defending his homeland as a sniper has weighed heavily on Matt's conscience. With the cause lost, the brothers desert--only to find upon their arrival home that Owen's farm has fallen into the hands of swindlers. When Owen accidentally kills a Union officer, Matt takes the blame. But now--facing a sham trial and a noose--he escapes to the west, where he saves the life of another fugitive down-and-outer. Both men are a breed apart from other outlaws. Neither kills for pleasure or steals for profit. But that doesn't matter to the cold-blooded men who are going to give them hell to pay--and get the same in return...."--Publisher marketing.